2017
DOI: 10.4103/jhrs.jhrs_21_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the bone morphogenetic protein-2 (BMP2) in the human cumulus cells as a biomarker of oocytes and embryo quality

Abstract: Background:The members of the transforming growth factor-B superfamily, as the bone morphogenetic proteins (BMPs) subfamily and anti-Müllerian hormone (AMH), play a role during follicular development, and the bone morphogenetic protein-2 (BMP2), AMH, and THY1 are expressed in ovaries.Aim:This study was designed to define whether or not the expressions of these proteins in human cumulus cells (CCs) can be used as predictors of the oocyte and embryo competence.Settings and Design:The study included nine female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…These are expressed in the ovary and regulate folliculogenesis [46-48]. The results of our recent study also demonstrate that there is a significant difference in the expression of BMP2 in the CCs of goodquality oocytes, and subsequently good embryos [49]. CCs associated either with developmentally incompetent or competent antral oocytes have been compared using microarrays with the whole transcriptome, and increased AMH gene expression has been shown to be correlated with oocyte competence [47].…”
Section: Discussionmentioning
confidence: 99%
“…These are expressed in the ovary and regulate folliculogenesis [46-48]. The results of our recent study also demonstrate that there is a significant difference in the expression of BMP2 in the CCs of goodquality oocytes, and subsequently good embryos [49]. CCs associated either with developmentally incompetent or competent antral oocytes have been compared using microarrays with the whole transcriptome, and increased AMH gene expression has been shown to be correlated with oocyte competence [47].…”
Section: Discussionmentioning
confidence: 99%
“…Increased BMP15 and GDF9 mRNA levels in CC correlated with oocyte maturation, fertilization, and embryo quality [72]. Higher oocyte quality was found in oocytes from follicles with high cumulus cell BMP2 expression levels [278]. Dysregulation of activin receptor-like kinase 6 (ALK6) in human GCs is correlated with decreased ovarian reserve [28].…”
Section: Bmp15mentioning
confidence: 99%
“…According to the transcriptome data of Zhang and co-workers 38 , this gene was found highly expressed during the meiotic, oogenesis, early granulosa, mural granulosa and late granulosa stages. This is not surprising given the well-proven expression of BMP2 in GC and germ cells 111 . Consistent with this, BMP2 was reported to be important for the follicular development 111 and a predictor marker of embryo quality 112 .…”
Section: Discussionmentioning
confidence: 88%
“…This is not surprising given the well-proven expression of BMP2 in GC and germ cells 111 . Consistent with this, BMP2 was reported to be important for the follicular development 111 and a predictor marker of embryo quality 112 . We demonstrated that genes like SOX4 and FZD5 are positively regulated by CBX2.2 and seem to have consistent high expressions during all stages of the FFGC.…”
Section: Discussionmentioning
confidence: 88%